2019
DOI: 10.1007/s00332-019-09592-x
|View full text |Cite
|
Sign up to set email alerts
|

The Exchange-Driven Growth Model: Basic Properties and Longtime Behavior

Abstract: The exchange-driven growth model describes a process in which pairs of clusters interact through the exchange of single monomers. The rate of exchange is given by an interaction kernel K which depends on the size of the two interacting clusters. Well-posedness of the model is established for kernels growing at most linearly and arbitrary initial data.The longtime behavior is established under a detailed balance condition on the kernel. The total mass density ̺, determined by the initial data, acts as an order … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
4
13
0
Order By: Relevance
“…Part of the results of this paper, namely those in Section 3, overlap with some of the results in [24] which were independently obtained. Actually the results in [24] cover a class of kernels wider than those considered in Section 3 of this paper.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Part of the results of this paper, namely those in Section 3, overlap with some of the results in [24] which were independently obtained. Actually the results in [24] cover a class of kernels wider than those considered in Section 3 of this paper.…”
supporting
confidence: 65%
“…This behavior was first demonstrated numerically in [8], where it was observed that the seemingly innocuous change in the kernel (K(j, 0) > 0) fundamentally alters the dynamical behavior, driving the system, towards a unique equilibrium (BD-like) instead of indefinite growth where the cluster densities eventually vanish (Smoluchowski-like when K(j, 0) = 0). For a large class of kernels this observation was recently proven in [24].…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In this section, our method is perturbative, for which reason we restrict to the complete graph, that is p(x, y) = 1 for all x = y. In this case, the mean-field limit from the N -particle system was derived in Grosskinsky and Jatuviriyapornchai (2019), and the limit equation was investigated in Schlichting (2019). Since positive curvature is know in the case of independent particles on the complete graph (Erbar and Maas, 2012), we expect that for c(µ x , µ y ) = T +c(µ x , µ y ) with bounded c : P(X ) × P(X ) → [0, ∞), we should also obtain positive entropic curvature for the non-linear models when T is sufficiently large.…”
Section: 2mentioning
confidence: 99%